(untitled) (Global Journal of Human-Social Science, 2014)
The principle objective of this study is to examine the culture of networks that are implicated in the production of culture, specifically as it pertains to artists’ design and use of digitally networked information and communication technologies (ICTs) for the production of artworks. The analysis in this study seeks to reveal a better understanding of the working practices that underpin artists’ creative engagements with new media while recognizing the significance of discursive continuities that inform such engagements. Theoretically, a case is presented for combining several theoretical perspectives into a multilayered conceptual framework for examining the circulation of power as it relates both to artistic creativity and to technological innovation.